The Kincses-Billege Apiary’s presentation according to the Hungarian Apicultural National Program (2013-2016) - Oravecz, Titanilla Éva (Animal welfare, Ethology and Housing Systems (AWETH), 2015)
In this work, our apiary’s 5 years development is presented in its market access method and the enrichment of its theoretical knowledge in regard to food safety. My main goal is to compare our apiary’s structure with the national average according to the Hungarian Apicultural National Program (2013-2016). The apiary’s production indicators, bee products and market activity are all demonstrated. The food safety aspect of honey production is investigated from the perspective of bee health care.. Regarding the topic of food safety i also present the environmental impacts, bee health care, hygiene of bee products and bee colonies as well as the path that the honey takes before it finally reaches its customers. I examinated consumer habits in different sales areas which may adumbrate whether the product will become a customer’s new favourite or not. The customers’ ethical, qualitative and commercial expectations are also presented as well as the effects of the honey adulteration scandals. The tasting opputinity of honey and bee products is a part of my presentation as i offer both national and foreign producers’ honey to taste personally, which may show you an unkown savour. I rely on professional researches, the Hungarian Bee-keeping Association and a local beekeeper’s theoretical and practical knowledge.